Analisis Pola Hubungan Konsultatif Pada Pengelolaan Pendapatan Asli Daerah Provinsi Sulawesi Tenggara Tahun Anggaran 2017-2019 - Akib, Mulyati; Mirosea, Nitri; Israyanti, Israyanti (Pascasarjana Universitas Halu Oleo, 2022)
How decentralisation build-up a sustainable local government? This study aims to determine the regional financial independence of Southeast Sulawesi Province for the 2017-2019 fiscal year. The type of data used in this research is quantitative data and qualitative data, the data source is secondary data from time series for the last five years (2017-2019). The data collection technique in this study was carried out by means of documentation. The analytical method used is descriptive analysis method.The results in this study indicate that the Southeast Sulawesi provincial government from 2015 to 2019 still has low regional financial independence where the percentage of the regional financial independence ratio is still between 25-50%, this shows that the government Southeast Sulawesi province still has a pattern of consultative relations with the central government, in which the central government has begun to reduce interference, because the regions are considered to be slightly more capable of implementing autonomy. According to Agency theory that Central Government as the principal while local government as the agent, the principal role has responsibility to support and accommodate the good governance.This is due to the fact that the Local-owned Source Income at the lower level than the amount of assistance from the central government, which is caused by the lack of revenue from the sources of regional original income for the province of Southeast Sulawesi. Southeast Sulawesi Province also still has sufficient capacity in implementing decentralization where the percentage ratio of the degree of decentralization shows an average figure above 20%, which is 23.1%. In this case, South East Sulawesi is a developing province which still have to induce the income in order to support the budgetary provincial government. This study contributes to develop the study of good governance government implementation in Indonesia.Keywords: Local owned-source revenue, Degree of Decentralization, Agency Theory, Good Governance